Probing the Entropic Effect in Molecular Noncovalent Interactions between Resin‐Bound Polybrominated Arenes and Small Substrates. Issue 9 (9th July 2018) - Yamamoto, Masanori; Obara, Miyuki; Ochi, Keisuke; Yamamoto, Atsushi; Takenaka, Katsuhiko; Tanaka, Tsunehiro; Sato, Kazunori
Abstract: The associative interaction between resin‐bound polybrominated arenes and small molecules was analyzed by using various spectroscopic techniques as well as a synthetic molecular model to establish the thermodynamics. The binding in acetonitrile was three orders of magnitude stronger than that in methanol, partly owing to the tertiary conformational gating of the resin that controls the entropic terms. By using the entropic superiority, the associative binding of up to 3×10 4 m −1 is achieved with the non‐biological system. A modified Hill plot for the quantitative analysis of bindings was also devised, which enabled the interactions at the molecular level to be elucidated. Abstract : Stuck on you : The associative interaction between resin‐bound polybrominated arenes and small molecules was analyzed by using various spectroscopic techniques as well as a synthetic molecular model to establish the thermodynamics (see figure). The associative interaction between poly1 and small molecules in acetonitrile is three orders of magnitude stronger than that in methanol. By using the entropic superiority, the associative binding of up to 3×10 4 m −1 is achieved with the non‐biological system. A modified Hill plot for the quantitative analysis of bindings was also devised, which enabled the interactions at the molecular level to be elucidated.